Less Income Inequality and More Growth - Are They Compatible? Part 2. The Distribution of Labour Income - Koske, Isabell (OECD Economics Department Working Papers, 2012)
This paper explores the role of macroeconomic factors and structural policies in shaping the distribution of labour income. Technological change and globalisation play at least some role in driving inequality patterns, but structural policy can also have an important influence on inequality outcomes, in particular through education and labour market policies. Drawing on empirical analysis of the links between structural policies and the distribution of labour income, the paper looks at potential policy trade-offs and complementarities with respect to the two policy objectives of lowering income inequality and raising economic growth. It concludes that many policies yield a double dividend in the sense that they contribute to achieving both goals simultaneously. This relates in particular to policies that facilitate the accumulation of human capital, that make educational achievement less dependent on personal and social circumstances, that reduce labour market dualism and that promote the labour market integration of immigrants and women